Mayská náboženská bratrstva v antropologické imaginaci - Jan Kapusta (AntropoWebzin, 2012)
Civil-religious hierarchies (also known as cargo systems or cofradías) in Mesoamerica have received considerable academic attention, namely in connection with the performance of feasts of saints, social organization of community, and prestige. In this paper the institution in Mayan culture is described and the anthropological theories focused on the problem of extensive expenditure during the feasts are discussed. Through an analysis of the dynamic history and contemporary progress of the institution, the paper takes issue with both the approaches of cultural essentialism or functionalism and colonial historicism or Marxism. In contrast to some of the recent anthropological developments, such as post-colonialism and post-structuralism, a phenomenological attitude which appreciates the relevance of expenditure as a psychosocial phenomenon of sacrifice is highlighted. In general terms, the aim of the study is to demonstrate the fruitfulness of diversity; drawing from particular social and individual circumstances and specific motives, anthropologists grasp the complexity of phenomena in a way which enables them to fulfil the age-old need for theoretical plurality and to make sense of nonsense. The conclusion discusses the emphasis of contemporary anthropology on anti-isolationism, anti-passivism, and anti-totalism.